Pengaruh Metode Latihan Gaya Komando dan Metode Latihan Gaya Eksplorasi Terhadap Keterampilan Dasar Bermain sepak bola SSB BINHAR Kerinci - DEKA ISMI MORI SAPUTRA (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2019)
The purpose of this study was to reveal the effect of the command method and exploration method as well as basic skills of playing football. Population of this study was football player of ssb binhar kerinci in totaling 90 people. sampling technique in this study used purposive sampling. This technique was done based on consideration of the researcher. Total sample in this research were 48 people. to measure the ability of playing football which consists of four forms of the test were dribling, short passed test, shooting and ball control. Analyis research data showed that: There was no significance difference between players who were trained using command method with players who were trained using exploration method